Keterlibatan Sukarni dalam Peristiwa Menjelang Proklamasi Kemerdekaan Tahun 1945 - Fahmi Muhamad Lutfi; Andri Nurjaman (UIN Sunan Gunung Djati Bandung, 2022)
This article discusses Sukarni's involvement in the events leading up to the proclamation of independence in 1945. Sukarni Kartodiwirdjo was a movement figure from young people or groups who had a nationalist spirit and played an active role in the Indonesian independence process. Sukarni was also one of the youth cadres formed directly by Soekarno so that he became a militant youth. The purpose of this article is to see Sukarni's involvement as a youth leader in the events leading up to the reading of the text of the proclamation of Indonesian independence in 1945. This article uses historical research methods consisting of heuristics, criticism, interpretation and historiography. The primary source was obtained from an interview with Emalia Iragiliati (daughter of Sukarni). The data obtained is presented in a narrative-descriptive way. The results showed that Sukarni played a major role in the youth movement leading up to the proclamation of independence, starting from the Menteng youth movement up to the proclamation of Indonesian independence. Debate due to differences in views of opinion occurred between the older and the younger groups regarding the time of reading the text of the proclamation. The young people led by Sukarni wanted to declare Indonesia's independence as soon as possible, this was also the background for the kidnapping of Soekarno-Hatta by the young people. Meanwhile, the elderly are being careful while coordinating with the Gunseikanbu or high-ranking Japanese military officials.